Nitric Oxide-Producing Cardiovascular Stent Coatings for Prevention of Thrombosis and Restenosis - Rao, Jingdong; Pan Bei, Ho; Yang, Yuhe; Liu, Yu; Lin, Haodong; Zhao, Xin (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular stenting is an effective method for treating cardiovascular diseases (CVDs), yet thrombosis and restenosis are the two major clinical complications which often lead to device failure.Nitric oxide (NO) has been proposed as a promising small molecule in improving the clinical performance of cardiovascular stents thanks to its anti-thrombosis and anti-restenosis ability, but its short half-life limits the full use of NO. To produce NO at lesion site with sufficient amount, NO producing coatings (including NO releasing and NO generating coatings) are fashioned. Its releasing strategy is achieved by introducing exogenous NO storage materials like NO donors, while the generating strategy utilizes the in vivo substances like S-nitrosothiols (RSNOs) to generate NO flux.NO producing stents are particularly promising in future clinical use due to their ability to store NO resources or to generate large NO flux in a controlled and efficient manner. In this review, we first introduce NO releasing and generating coatings for prevention of thrombosis and restenosis. We then discuss the advantages and drawbacks on releasing and generating aspects, where possible 2 further developments are suggested.